1985
DOI: 10.1136/pgmj.61.718.757
|View full text |Cite
|
Sign up to set email alerts
|

Primary nongestational choriocarcinoma of the ovary

Abstract: Summary Primary choriocarcinoma of the ovary arising, presumably, from a germ cell is extremely rare. The patient, a 16 year old girl who presented with dysuria and frequency of micturition developed fatal haemoperitoneum due to rupture of a pure primary nongestational ovarian choriocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…For an ovarian choriocarcinoma to be unequivocally derived from germ cells, it should be diagnosed in a nonpregnant woman or prepubertal girl. 6 With no evidence of ovarian, tubal or uterine pregnancy, it is difficult to establish the present case as ovarian gestational choriocarcinoma or a metastasis from a uterine or tubal choriocarcinoma that has regressed. It is important to distinguish between gestational and nongestational choriocarcinomas, since nongestational choriocarcinomas have been found to be resistant to single agent chemotherapy, have a worse prognosis, and therefore require aggressive combination chemotherapy.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…For an ovarian choriocarcinoma to be unequivocally derived from germ cells, it should be diagnosed in a nonpregnant woman or prepubertal girl. 6 With no evidence of ovarian, tubal or uterine pregnancy, it is difficult to establish the present case as ovarian gestational choriocarcinoma or a metastasis from a uterine or tubal choriocarcinoma that has regressed. It is important to distinguish between gestational and nongestational choriocarcinomas, since nongestational choriocarcinomas have been found to be resistant to single agent chemotherapy, have a worse prognosis, and therefore require aggressive combination chemotherapy.…”
Section: Discussionmentioning
confidence: 85%
“…5 P u re primary nongestational ovarian choriocarcinoma of the ovary is extremely rare. 6 Choriocarcinoma of the ovary is a highly malignant ovarian tumor which is characterized pathologically by the presence of trophoblastic malignant cells, and biochemically by the production of the pregnancy hormone human chorionic gonadotropin (hCG) in absence of pregnancy. Choriocarcinoma is a rapidly invasive, widely metastatic, human chorionic gonadotropin (hCG) producing neoplasm which usually has an intrauterine location.…”
mentioning
confidence: 99%
“…When a pure choriocarcinoma occurs in a woman of reproductive age, however, the determination of its origin is very difficult by histology alone. Before the 1990s, the diagnosis of non‐gestational choriocarcinoma was based primarily on a history of virginity and on the premenarchal or postmenopausal status of the patient, whereas molecular techniques were not frequently used to determine tumor origin 1,6 , 9,11 , 12,14 , 16,17 . More recently, however, several cases of pure ovarian choriocarcinoma have been diagnosed using DNA polymorphism analysis 2,5 , 8,10,19 .…”
Section: Discussionmentioning
confidence: 99%
“… 1,2,4 Chou et al reported the first case of NGCO successfully treated with high‐dose chemotherapy and autologous bone marrow transplantation (ABMT) together with a hysterectomy and bilateral salpingo‐oophorectomy. 4 Because the age range of NGCO patients is usually between 7 months and 35 years with a mean of about 13 years, 3 reproductive capacity should be retained as much as possible in successfully treated cases. Wu et al carried out preservation of fertility in 28 patients with malignant germ cell tumors (GCT) of the ovary, including six recurrent cases, and they achieved persistent remission in 22 cases (78.6%).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, non‐gestational choriocarcinoma of the ovary (NGCO) is an exceedingly rare germ cell neoplasm. 1–3 Non‐gestational choriocarcinoma has a worse prognosis than gestational neoplasms and only occasional survivals have been reported in advanced cases. 1,2,4 We report a case of metastatic NGCO successfully treated with combined high‐dose chemotherapy and autologous bone marrow stem cell transplantation with preservation of the reproductive system.…”
mentioning
confidence: 99%